Tricaproin Isolated From Simarouba glauca Inhibits the Growth of Human Colorectal Carcinoma Cell Lines by Targeting Class-1 Histone Deacetylases - Jose, Asha; Chaitanya, Motamari V. N. L.; Kannan, Elango; Madhunapantula, SubbaRao V. (Frontiers in Pharmacology, 2018)
While anticancer properties of Simarouba glauca (SG, commonly known as Paradise tree) are well documented in ancient literature, the underlying mechanisms leading to cancer cell death begin to emerge very recently. The leaves of SG have been used as potential source of anticancer agents in traditional medicine. Recently attempts have been made to isolate anticancer agents from the leaves of SG using solvent extraction, which identified quassinoids as the molecules with tumoricidal activity. However, it is not known whether the anti-cancer potential of SG leaves is just because of quassinoids alone or any other phytochemicals also contribute for the potency of SG leaf extracts. Therefore, SG leaves were first extracted with hexane, dichloromethane, chloroform and 70% ethanol, and anti-cancer potential (for inhibiting colorectal cancer (CRC) cells HCT-116 and HCT-15 proliferation) determined using Sulforhodamine-B (SRB) assay. The chloroform fraction with maximal anticancer activity was further fractionated by activity-guided isolation procedure and structure of the most potent compound determined using spectral analysis. Analysis of the structural characterization data showed the presence of tricaproin (TCN). TCN inhibited CRC cells growth in a time- and dose dependent manner but not the normal cell line BEAS-2B. Mechanistically, TCN reduced oncogenic Class-I Histone deacetylases (HDACs) activity, followed by inducing apoptosis in cells. In conclusion, the anti-cancer potential of SG is in part due to the presence of TCN in the leaves.